Changes in the Heart Rate of Sniffer Dogs Trained for Detection of Lung Cancer - Riedlova, Petra; Tavandzis, Spiros; Kana, Josef; Ostrizkova, Silvie; Kramna, Dagmar; Krajcir, Libor; Kanova, Tereza; Lastikova, Simona; Tomaskova, Hana; Roubec, Jaromir (Diagnostics (Basel, Switzerland), 2023)
BACKGROUND: Lung carcinoma is one of the most common malignancies worldwide. At present, unfortunately, there are no markers that would allow early identification of this tumor in the preclinical or early clinical stage. The use of sniffer dogs has been reported to show some promise in early diagnosis of this type of cancer Aim: This study aimed to evaluate the possibility of utilizing changes in the heart rate of sniffer dogs (which increases when finding a positive sample) in tumor detection. METHODS: This double-blinded pilot study included two sniffer dogs. A chest strap was fastened on the dog's chests for heart rate monitoring while they were examining samples and heart rate was recorded. Test parameters (sensitivity, specificity, positive and negative predictive values) were then calculated, evaluating performances based on (i) the dog's indications according to their training and (ii) the changes in their heart rates. RESULTS: Calculation according to the dog's indications revealed an overall sensitivity of 95.2% accompanied by a specificity of 81.8%, a PPV of 93.7%, and an NPV of 85.7%, respectively. These results were not significantly different from those evaluated by heart rate; heart rate monitoring was, however, burdened with a relatively high proportion of invalid experiments in which heart rate measurement failed. When the method of calculation was changed from rounds to individual samples, the test parameters further increased. CONCLUSIONS: This pilot study confirmed the hypothesis that heart rate increases in trained sniffer dogs when encountering samples from tumor-positive patients but remains unchanged when only negative samples are present. The reliability of results based on heart rate increase is similar to that obtained by a dog's indications and, if the limitation represented by technical issues is overcome, it could serve as a valuable verification method.
Keywords: detection; heart rate; lung cancer; sniffer dog; diagnosis